(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article discusses the unique, lexical, stylistic features of the colloquial style, the syntax of this colloquial speech, the special scientific-research works on the lexicon of the colloquial speech, and the tasks to be performed in the future.